MECHANISMS FOR FINANCING STARTUP PROJECTS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article provides a comprehensive analysis of the mechanisms for financing startup projects, their economic essence, forms, and practical significance. In the context of a modern innovative economy, startups serve as a key driver of technological progress, economic growth, and job creation. However, one of the most critical challenges for startups is access to financial resources. The article examines both traditional and modern startup financing mechanisms, including own funds (bootstrapping), bank loans, venture capital, business angels, crowdfunding, government grants, and the participation of international financial institutions. In addition, the paper analyzes the current state of startup financing in Uzbekistan, identifies existing problems, and proposes practical recommendations for improving financing mechanisms and strengthening the startup ecosystem.